The emergence of China : opportunities and challenges for Latin America and the Caribbean - Devlin, Robert; Estevadeordal, Antoni; Rodríguez-Clare, Andrés (Inter-American Development Bank ; Harvard University Press, 2006)
"The Emergence of China: Opportunities and Challenges for Latin America and the Caribbean provides a comprehensive overview of China's economic policy and performance over recent decades and contrasts them with the Latin American experience. What are the underlying factors behind China's competitive edge? What are the strategic implications of China's rise for growth and development in Latin America? These questions open new avenues for thinking about revitalizing development strategies in Latin America in the face of China's successful development and reduction of poverty. This insightful report is a must-read for analysts, policymakers, and development practitioners, not only in Latin America and the Caribbean, but wherever China's presence is being felt."--Jacket